دراسة تحليلية لأثر المستوى التعليمي للام على وفيات الأطفال الرضع في الجزائر - دكاكن, نادية; طعبة, عمر (جامعة الوادي - University of Eloued, 2023)
ملخص: تهدف هذه الدراسة إلى معرفة أهمية المستوى التعليمي للأمهات في خفض متوسط وفيات الأطفال الرضع في الجزائر وذلك من خلال القياس الكمي لأثر المستوى التعليمي للام على وفيات الأطفال الأقل من 365 يوم، لتحقيق ذلك تم إتباع المنهج الوصفي التحليلي في وصف و تحليل بيانات قاعدة معطيات المسح العنقودي المتعدد المؤشراتMICS6 المنجز سنة 2018-2019 بالجزائر. خلصت نتائج الدراسة بعد تطبيق أسلوب الانحدار اللوجستي الثنائي أن كلما ارتفع المستوى التعليمي للام من دون مستوى إلى المستوى العالي سينقص ارجحية وفيات الرضع بـ0,178 مرة أي عند الارتفاع من دون المستوى إلى المستوى العالي سيخفض احتمال وفاة رضيعها بنسبة 82,2%. Abstract: This study aims to know the importance of mother’s educational level in reducing the average infant mortality rate in Algeria, through quantitative measurement of the impact of the mother’s educational level on deaths of children less than 365 days old. To achieve this, the descriptive analytical approach was followed in describing and analyzing the data of Multiple Indicator Cluster (MIC6) conducted in the year 2018-2019 in Algeria. The results of the study, after applying the method of binary logistic regression, concluded that whenever the educational level of the mother increased from below the level to the high level, the probability of infant mortality would decrease by 0.178 time. That is when we rising from below the level to the high level, the probability of her infant dying would be reduced by 82.2%.
مقال
Keywords: مستوى تعليمي ؛ رضع ؛ مسح ؛ انحدار لوجستي; Educational level; Infants; Survey; Logistic regression